A reliability study of a lactate profile test for running in the water with a "wet vest" - Stallman, R. K.; Naess, G.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming X, 2006)
This study was a test-retest examination of the reliability of a test protocol for generating a blood lactate profile for running in the water with the wet vest. The protocol was a duplication of the protocol used in our laboratory for treadmill running except that \ load was controlled by continuous monitoring of HR. Blood lactate values were determined for HR levels of 120, 130, 140, 150,160 and if necessary, 170 and 180 BPM. Fifteen subjects performed test with 1-3 days between tests. Results demonstrated that a) 1 protocol was well suited to use with the wet vest under field conditions 2) the intra-test Variation in HR was minimal (mean SD for all tests, all subjects, 1.6 BPM) and c) the reliability of the repeated test was high (mean coefficient of Variation, 1.46; p>0.05).